Interferon regulatory factor 1 is essential for pathogenic CD8+ T cell migration and retention in the brain during experimental cerebral malaria. (18th January 2018) - Gun, Sin Yee; Claser, Carla; Teo, Teck Hui; Howland, Shanshan W.; Poh, Chek Meng; Chye, Rebecca Ren Ying; Ng, Lisa F.P.; Rénia, Laurent
Abstract: Host immune response has a key role in controlling the progression of malaria infection. In the well‐established murine model of experimental cerebral malaria (ECM) with Plasmodium berghei ANKA infection, proinflammatory Th1 and CD8+ T cell response are essential for disease development. Interferon regulatory factor 1 (IRF1) is a transcription factor that promotes Th1 responses, and its absence was previously shown to protect from ECM death. Yet the exact mechanism of protection remains unknown. Here we demonstrated that IRF1‐deficient mice (IRF1 knockout) were protected from ECM death despite displaying early neurological signs. Resistance to ECM death was a result of reduced parasite sequestration and pathogenic CD8+ T cells in the brain. Further analysis revealed that IRF1 deficiency suppress interferon‐γ production and delayed CD8+ T cell proliferation. CXCR3 expression was found to be decreased in pathogenic CD8+ T cells, which limited their migration to the brain. In addition, reduced expression of adhesion molecules by brain endothelial cells hampered leucocyte retention in the brain. Taken together, these factors limited sequestration of pathogenic CD8+ T cells and consequently its ability to induce extensive damage to the blood–brain barrier.